1995
DOI: 10.1118/1.597522
|View full text |Cite
|
Sign up to set email alerts
|

The 200‐MeV proton therapy project at the Paul Scherrer Institute: Conceptual design and practical realization

Abstract: The new proton therapy facility is being assembled at the Paul Scherrer Institute (PSI). The beam delivered by the PSI sector cyclotron can be split and brought into a new hall where it is degraded from 590 MeV down to an energy in the range of 85-270 MeV. A new beam line following the degrader is used to clean the low-energetic beam in phase space and momentum band. The analyzed beam is then injected into a compact isocentric gantry, where it is applied to the patient using a new dynamic treatment modality, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
379
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 548 publications
(382 citation statements)
references
References 0 publications
1
379
0
2
Order By: Relevance
“…As a result of an improved dose distribution [4,5] and of advances in delivery techniques [6,7], protons are gaining increasing interest worldwide as an elective treatment for specific types of tumors and the number of dedicated proton therapy facilities is rapidly growing [8]. The need of proton dosimetry standardization and of improvement of dosimetric accuracy have motivated the implementation of international dosimetry protocols [9,10], and a challenging optimization of detector technology.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of an improved dose distribution [4,5] and of advances in delivery techniques [6,7], protons are gaining increasing interest worldwide as an elective treatment for specific types of tumors and the number of dedicated proton therapy facilities is rapidly growing [8]. The need of proton dosimetry standardization and of improvement of dosimetric accuracy have motivated the implementation of international dosimetry protocols [9,10], and a challenging optimization of detector technology.…”
Section: Introductionmentioning
confidence: 99%
“…The usual beam lines and gantries are located at the end of the linac. It can been shown that the time and intensity structure of a cyclinac is better suited to the active dose distribution approach, called "spot scanning" and developed at PSI [7] than those produced by cyclotrons and synchrotrons. A cyclinac is intended to be the heart of IDRA, the "Institute for Diagnostic and RAdiotherapy", which is a multipurpose facility for the production of both radiopharmaceuticals for diagnostic and therapy, and high-energy protons for the radiotherapy of superficial and deep-seated tumours (Fig.…”
Section: The Cyclinac Approach To Hadrontherapymentioning
confidence: 99%
“…The MOPI detector covers a sensitive area of 12.8 x 12.8 cm 2 and is divided in two chambers separated by a common cathode plane, as shown in Fig.3. The anode plane of each chamber is segmented in 256 strips, resulting in a pitch of 0.5 mm, oriented along the vertical and horizontal directions.…”
Section: The Mopi Detectormentioning
confidence: 99%